Tujuan Pembelajaran Dalam Pendidikan Kristen Berdasarkan 2 Timotius 3:16 - Firman Panjaitan (Sekolah Tinggi Teologi Anugrah Indonesia, 2022)
The general problem in today's education pattern lies in the imbalance between the cognitive, affective and psychomotor domains. Education tends to focus on the cognitive domain and ignores the affective and psychomotor domains, so that students' self-worth becomes